2021
DOI: 10.3389/fpsyg.2021.719596
|View full text |Cite
|
Sign up to set email alerts
|

‘I Get High With a Little Help From My Friends’ - How Raves Can Invoke Identity Fusion and Lasting Co-operation via Transformative Experiences

Abstract: Psychoactive drugs have been central to many human group rituals throughout modern human evolution. Despite such experiences often being inherently social, bonding and associated prosocial behaviors have rarely been empirically tested as an outcome. Here we investigate a novel measure of the mechanisms that generate altered states of consciousness during group rituals, the 4Ds: dance, drums, sleep deprivation, and drugs. We conducted a retrospective online survey examining experiences at a highly ritualized cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…Connectedness as a construct spanning these three domains has not been measured, or systematically studied. Yet the experience of feeling connected to self and others, and the interconnected living world, is commonly described by psychedelic 'users'-whether they use be in ceremonial (Dobkin de Rios 1984;Gearin 2016;Kettner et al 2021;La Barre 1938/1975Tramacchi 2000), festival (Forstmann et al 2020;St John 2009), dance party or 'rave' (Newson et al 2021) or therapeutic contexts (Agin-Liebes et al 2021;Argento et al 2019;Belser et al 2017;Loizaga-Velder and Verres 2014;Noorani et al 2018;Swift et al 2017;Thomas et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Connectedness as a construct spanning these three domains has not been measured, or systematically studied. Yet the experience of feeling connected to self and others, and the interconnected living world, is commonly described by psychedelic 'users'-whether they use be in ceremonial (Dobkin de Rios 1984;Gearin 2016;Kettner et al 2021;La Barre 1938/1975Tramacchi 2000), festival (Forstmann et al 2020;St John 2009), dance party or 'rave' (Newson et al 2021) or therapeutic contexts (Agin-Liebes et al 2021;Argento et al 2019;Belser et al 2017;Loizaga-Velder and Verres 2014;Noorani et al 2018;Swift et al 2017;Thomas et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In psychedelics research, the process of self-transcendence is often referred to as 'ego dissolution' (Nour, Evans, Nutt, & Carhart-Harris, 2016). However, this term may confuse whether ego diminishment or ego expansion takes place (Newson, Khurana, Cazorla, & van Mulukom, 2021):…”
Section: Self-transcendencementioning
confidence: 99%
“…We suggest here that in religious and artistic experiences particularly, it is self-expansion rather than selfdiminishment that takes place (see also the 'Broaden and Build' hypothesis, Fredrickson, 2004). In the context of awe-inspiring psychedelic trips as well as rave experiences, it has been found that selfexpansion (measured by the AWE-S subscale 'connectedness'; Yaden et al, 2018) rather than selfdiminishment (measured by the AWE-S subscale 'self-diminishment'; Yaden et al, 2018) predicted connectedness to nature or fellow ravers up to five years after the experience (Newson et al, 2021;van Mulukom, Patterson, & van Elk, 2020). A further investigation of self-diminishment has demonstrated that there may be three dimensions to self-diminishment which may be conflated by some self-diminishment scales: perceived self-size (feeling metaphorically small), vastness relative to self, and small self-perspective (i.e., a sense of proportion about one's daily concerns; feeling one's day-to-day concerns as trivial in the grand scheme of things) (Tyson, Hornsey, & Barlow, 2021).…”
Section: Self-transcendencementioning
confidence: 99%
See 2 more Smart Citations